2023
DOI: 10.31989/ffhd.v13i11.1057
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of Quercus salicina blume leaves aqueous extracts against cadmium-induced oxidative stress and cell cytotoxicity in HK-2 cells

Yun Jeong Kim,
Joo-Won Lee,
Ae-son Om

Abstract: Background: Quercus salicina Blume is an evergreen plant growing southern parts of Korea and Japan, and has been used for the treatment of dysentery, dermatitis, and hemorrhage from possible effects such as anti-inflammatory, anti-endemic and litholytic activities. We investigated the underlying mechanisms of Quercus salicina Blume leaf extracts (QS) protection against cadmium treatment utilizing human kidney origin HK-2 cells.Methods: To ascertain the functional constituents of the hot water-extracted QS, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…According to the Functional Food Center (FFC), functional foods (FFs) are foods obtained from nature or derived from food processing that contain a suitable amount of biologically active compounds; these compounds provide health benefits and reduce the risk or symptoms of diseases [8]. Functional foods and bioactive compounds can be helpful in treating various clinical problems, including obesity [9], oxidative stress [10], inflammation [11][12], blood cholesterol [13], and so on [14][15]. Many studies have demonstrated that natural compounds in medicinal herbs can reduce the risk of GC [16][17].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Functional Food Center (FFC), functional foods (FFs) are foods obtained from nature or derived from food processing that contain a suitable amount of biologically active compounds; these compounds provide health benefits and reduce the risk or symptoms of diseases [8]. Functional foods and bioactive compounds can be helpful in treating various clinical problems, including obesity [9], oxidative stress [10], inflammation [11][12], blood cholesterol [13], and so on [14][15]. Many studies have demonstrated that natural compounds in medicinal herbs can reduce the risk of GC [16][17].…”
Section: Introductionmentioning
confidence: 99%